2011
DOI: 10.3201/eid1705.101309
|View full text |Cite
|
Sign up to set email alerts
|

Human Intraocular Filariasis Caused byPelecitussp. Nematode, Brazil

Abstract: A male nematode was extracted from iris fibers of a man from the Brazilian Amazon region. This nematode belonged to the genus Pelecitus but was distinct from the 16 known species in this genus. Similarities with Pelecitus spp. from neotropical birds suggested an avian origin for this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In South America, fifty sporadic cases have been reported: pulmonary (Venezuela, Colombia, Brazil, Argentina) and subcutaneous/ocular nodules (Brazil, Chile) [8,51,52]. D. immitis implicated in human ocular dirofilariasis was classified as a more virulent strain [51]. Fortunately, the phylogenetic analysis we conducted indicated that it is not the virulent D. immitis (Figures 3 and 4) which could explain the lower prevalence of human cases [39].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In South America, fifty sporadic cases have been reported: pulmonary (Venezuela, Colombia, Brazil, Argentina) and subcutaneous/ocular nodules (Brazil, Chile) [8,51,52]. D. immitis implicated in human ocular dirofilariasis was classified as a more virulent strain [51]. Fortunately, the phylogenetic analysis we conducted indicated that it is not the virulent D. immitis (Figures 3 and 4) which could explain the lower prevalence of human cases [39].…”
Section: Discussionmentioning
confidence: 86%
“…Since humans can be infected, doctors could be confronted with this parasitosis, which is mainly characterized by the presence of pulmonary nodules. In South America, fifty sporadic cases have been reported: pulmonary (Venezuela, Colombia, Brazil, Argentina) and subcutaneous/ocular nodules (Brazil, Chile) [8,51,52]. D. immitis implicated in human ocular dirofilariasis was classified as a more virulent strain [51].…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of zoonoses caused by mammalian filariae belonging to the two subfamilies Onchocercinae and Dirofilariinae have been identified [30]. Two rare zoonoses have also been described: one caused by Meningonema peruzzii, from the subfamily Splendidofilariinae [31], and another caused by Pelicitus sp., an avian filaria [32].…”
Section: Biology Of Filariae and Their Endosymbiont Wolbachiamentioning
confidence: 99%
“…[4-7]. The life cycles and the animal reservoir hosts for many of these species are still poorly known.…”
Section: Introductionmentioning
confidence: 99%